Homeopathic Treatment of Pododermatitis in Magellanic Penguins (Spheniscus magellanicus) - Narita, Franscinne Brait; Scardoeli, Bruna; Gallo Neto, Hugo; Coelho, Cidéli de Paula (Homeopathy, 2020)
Background Problems with the feet are common in penguins, with a particular predisposition to pododermatitis. This condition usually occurs due to the changes in normal activity that result from being held captive, but its precise pathogenesis is still undetermined.Methods/Patients This veterinary case study reports the use of oral homeopathic treatment on acute and chronic pododermatitis in five Magellanic penguins in a zoological park setting. During treatment, the patients remained in the penguins' living area, and the effect of the treatment on the progression of their lesions was assessed visually once weekly. The treatment consisted of a combination of Arnica montana and Calcarea carbonica.Results After treatment, the appearance of the lesions had noticeably improved: in the majority of penguins there was no longer evidence of infection or edema in the feet. The rate of recovery depended on the initial severity of the lesion. Those penguins that still showed signs of infection nevertheless exhibited a clear diminution of the size and thickness of the lesions. Homeopathic treatment did not cause any side effects.Conclusion Homeopathy offers a useful treatment option for pododermatitis in captive penguins, with easy administration and without side effects.
Keywords: veterinary homeopathy; penguins; pododermatitis; zoological park